Uppsala 1968 and the Contemporary Theological Situation - Thomas, Madathilparampil Mamen (Scottish journal of theology, 1970)
The criticism that the Uppsala Assembly of the World Council of Churches did not give sufficient attention to theology is justified. But this fact should be set within the perspective of the deep crisis which the theological world as a whole faces today, and which constitutes the contemporary theological situation. What are some of the factors which have contributed to this situation? One may mention three of them.